(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The purpose of this study was to evaluate the cognition of healthcare workers and clinical medical students on nicotine and its replacement therapy in Chengdu. Questionnaires were distributed to the medical students at Chengdu University Medical College and the medical staff in the Affiliated Hospital of Chengdu University as the basis of the project research. Then the statistical analysis of the data was used to give a specific research evaluation of nicotine and its replacement therapy. A total of 217 medical staff and 332 medical students were included in the analysis. In our study, overall awareness of nicotine replacement therapy was low, with only 3.6 percent of smokers using it. 54.2 percent of quitters would not recommend e-cigarettes to long-term smokers who refuse to take medication. The domestic understanding of nicotine replacement therapy and the e-cigarette was not also comprehensive. Only 45.8% of healthcare workers recommend nicotine replacement therapy and e-cigarettes to patients who want to quit smoking. In conclusion, healthcare workers have insufficient awareness about nicotine, nicotine replacement therapy and e-cigarettes. Accurate and comprehensive information about these substances should be provided to healthcare professionals to provide effective patient care and advice.